Consider the equation : $$ y[n]-\frac{1}{2}y[n-1]=x[n] $$ where $x[n]:=\left(\frac{1}{3}\right)^{n}u[n]$. First, I founded the homogenous solution $y_{h}:=A\frac{1}{2^{n}}$ $$ y_{h}[n]=\frac{1}{2^{n}}y[0] $$ where I insist $A=y[0]$. Furthermore, The particular solution is given of the form $y_{p}[n]:=B\left(\frac{1}{3}\right)^{n}$ I shall determine $B$ as follow : $$ B\left(\frac{1}{3}\right)^{n}u[n]-\frac{1}{2}B\left(\frac{1}{3}\right)^{n-1}u[n-1]=\left(\frac{1}{3}\right)^{n}u[n] $$ \begin{align*} \implies B&=\frac{\displaystyle\left(\frac{1}{3}\right)^{n}u[n]}{\displaystyle\left(\frac{1}{3}\right)^{n}u[n]-\frac{1}{2}\displaystyle\left(\frac{1}{3}\right)^{n-1}u[n-1]}\\ \\ &=\frac{\displaystyle\left(\frac{1}{3}\right)^{n}}{\displaystyle\left(\frac{1}{3}\right)^{n}-\displaystyle\frac{1}{2}\left(\frac{1}{3}\right)^{n-1}}\\ \\ &=-2 \end{align*}

So now that we have $B=-2$, We are given the initial rest condition so what I did was sub $n=0$ in difference equation $$ y[0]-\frac{1}{2}y[-1]=x[0] $$ $$ \implies y[0]=1 $$ $$ **\text{So this means $A=y[0]=1$}** $$ However, the major issue is that : $$ y[0]-\frac{1}{2}y[-1]=x[0] $$ $$ \implies y[0]=1 $$ $$ \implies y[n]:= y_{h}[n]+y_{p}[n] \implies y[0]=y_{h}[0]+y_{p}[0]=1 $$ $$ \implies A\left(\frac{1}{2}\right)^{0} -2\left(\frac{1}{3}\right)^{0}=1 $$ $$ \implies A=3 $$ So I have $A=1$ and $A=3$, an obvious contradiction and I hope someone can help me

  • $\begingroup$ You never say what your actual initial condition (I assume $y[0]$) is. Nor do you say if this is a typical problem where $y[-1]$ is undefined. $\endgroup$
    – TimWescott
    Mar 5, 2021 at 0:56
  • $\begingroup$ The idea is that applying rest condition gives $y[0]-0.5y[-1]=x[0]$ but $x[0]=(1/3)^{0}=0$ and $y[-1]$ is $0$ so $y[0]=1$. @TimWescott $\endgroup$
    – SPARSE
    Mar 5, 2021 at 7:58
  • 1
    $\begingroup$ I don't see why you can't assume that $y[n] = 0$ for all $n<0$. The solution will for $y[n]$ will involve $u[n]$ too. $\endgroup$
    – IanJ
    Mar 6, 2021 at 19:32

2 Answers 2


From the comments under Tim Wescott's answer, it seems that there is still some confusion concerning the correct way to solve such problems. Let's consider the non-homogeneous difference equation (DE)

$$y[n]-p y[n-1]=q^n,\qquad p\neq q\tag{1}$$

with initial value $y[-1]=c$. Note that initially we don't restrict the forcing function on the right-hand side of $(1)$ to equal zero for $n<0$.

As correctly shown in the OP, the general solution to the homogeneous DE has the form


which is also called the natural response, and a particular solution (forced response) of $(1)$ is given by


The constant $B$ is determined by substituting $(3)$ into $(1)$:


from which we obtain $B=\frac{q}{q-p}$. Consequently, the general solution of the non-homogeneous DE $(1)$ is


Note that the solution $(5)$ is valid for all values of $n$.

The value of $A$ is determined by the initial condition $y[-1]=c$. Substituting $n=-1$ into $(5)$ and setting it equal to $c$ results in


The solution to the initial value problem is hence given by


We now only consider values $n\ge 0$, simply because that's the range we're interested in.

Note that the term $cp^{n+1}$ in $(7)$ is the zero-input response (ZIR), and the remaining term is the zero-state response (ZSR).

From an engineering point of view, composing the solution into a ZSR and a ZIR appears more natural and more useful than the classical decomposition into a homogeneous and a particular solution, because the decomposition of the solution into ZSR and ZIR separates the contributions arising from an external input and from internal conditions, respectively.


where I insist $A=y[0]$

There's your problem. $y[n] = y_h[n] + y_p[n]$, so $y[0]$ must equal $y_h[0] + y_p[0] = A + B$.

Can you take it from here?

  • $\begingroup$ Wait, I was just noticing that in my finding of $B$, don't you think the entire problem is ill-posed because there are two different values for $B$ if $n=0$ and $n>0$. I am referring to my derivation of finding $B$ where I wrongly removed $u[n]$ and $u[n-1]$. $\endgroup$
    – SPARSE
    Mar 4, 2021 at 22:21
  • $\begingroup$ But here $A=A+B \implies B=0$ which is not the case according to OP? $\endgroup$ Mar 4, 2021 at 23:26
  • $\begingroup$ The OP is saying $y[0]-\frac{1}{2}y[-1]=x[0]$. You can't do that -- $y[-1]$ is undefined. All you know about $y$ (if the problem is framed in the usual way) is that $y[0] = 1$ is true. $\endgroup$
    – TimWescott
    Mar 5, 2021 at 1:51
  • $\begingroup$ Well, and the given difference equation. The difference equation establishes $B$, $y[0] = 1$, and some arithmetic, establishes $A$. $\endgroup$
    – TimWescott
    Mar 5, 2021 at 2:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.